Carbonaceous nanomaterials for phototherapy: a review - Gurbuz, Betul; Ayan, Sumeyra; Bozlar, Micheal; Ustundag, Cem Bulent (SPRINGERNATURE, 2020)
Nowadays, cancer can be described as a common disease of our society. According to the World Health Organization, 8.2 million people in the world (approximately 0.11% of worldwide population) die each year from cancer. A major challenge for cancer therapy remains in developing cancer treatments with less toxicity. Conducted worldwide, over a period of 25 years, the outcomes of preclinical and clinical studies established phototherapy (PT) as a useful treatment for some cancer types. Photodynamic therapy (PDT) and photothermal therapy (PTT) are two critical PT treatments in order to damage tumor cells. PDT utilizes a combination of drugs, photosensitive molecules also known as photosensitizers (PSs), and visible light of an appropriate wavelength in order to activate drugs. PTT employs agents to generate heat from illumination. Most clinically confirmed PSs target superficial lesions because of their limited effects on cancerous tissues, and consequently, this approach causes non-effective therapy to deep-seated cancerous tissues. Combination of PDT and PTT with carbonaceous nanomaterials (CNs) offers additional active complementary and supplementary roles for deep tumors in cancer therapy. The effective delivery of therapeutic molecules into the cancer cell, containing surfaces, optimum sizes, and shapes of the CNs that are able to be enhanced with homing ligands and utilizable interactions. CNs have significant potential for biomedical applications, due to their unique well-designed size, composition, biocompatibility, and functionalities. CNs including graphene, graphene oxide (GO), carbon nanotubes (CNTs), and fullerenes (C-60) can act as efficient PS carriers for cancer treatment. Each material has advantages and disadvantages such as degradability, solubility, and drug loading capacity for cancer therapy. This review discusses the theranostic applications of CNs. Benefiting from other researches, CNs will be categorized with regard to their application and effectiveness in PT. The chemical modification of the mentioned substances before their biomedical applications will be briefly discussed. The advantages and limitations of these nanomaterials (NMs) provide a new perspective on improving cancer therapy using these CNs.
Keywords: Carbonaceous nanomaterials; Cancer treatment; Phototherapy; Photodynamic therapy; Photothermal therapy; UP-CONVERSION NANOPARTICLES; REDUCED GRAPHENE OXIDE; DRUG-DELIVERY; IN-VITRO; SINGLET OXYGEN; CANCER-THERAPY; ANTICANCER ACTIVITY; METHYLENE-BLUE; QUANTUM YIELD; Materials Science